PSYCHOLOGICAL FEATURES OF THE FORMATION OF CREATIVITY IN STUDENTS - Ramazanov Jahangir Jalolovich; Sayfullayeva Malika Abdumannon qizi (Web of Journals Publishing, 2024)
The existing pedagogical practice in the new social conditions cannot be implemented without a deep understanding of methodological and practical problems from a theoretical point of view, since without solving these problems there would be no influence of education and upbringing. This article provides information about the role of creativity in students' activities, its significance, degree of study, relevance to date, methods and implementation in the practice of studying students' creative activities.
Keywords: Creativity, creative motivation, motivation, approach, abilities, creative education, personal education. youth, the development of an individual society, knowledge, skills.